Sistem Informasi Surat Menyurat Berbasis Website Di Kantor Kecamatan Cikarang Utara - Ari Yuneldi; Rita Krisdhayanti (DPPM Universitas Pelita Bangsa, 2022)
Letters are one of the most important communication media in an agency, company or organization that can be used internally and externally as needed. Correspondence activities carried out by North Cikarang sub-district employees still use the conventional method, namely storing data in the form of sheets of paper that are stacked in a storage cupboard. Data storage by stacking the letter sheets has several weaknesses that result in data being lost. The purpose of this study is to facilitate the work of the sub-district head or staff for the disposition process and data management, in the form of incoming and outgoing letters that run at the North Cikarang District Office. The research started from literature studies from various books and journals, and field studies through direct observation. The research method used in the development of this system is the waterfall method. The results obtained are that the researchers succeeded in implementing the designed system with a success rate of 80% as evidenced by blackbox testing. There are five features in the incoming and outgoing mail information system, namely incoming mail management, outgoing mail management, mail disposition management, section data management and user data management. Keywords: North Cikarang District, Information System, Waterfall, Correspondence, Mail Information System